Information Competences - Students' Perspective - Pavlina, Krešimir (Array, 2014)
Modern society is characterized by an increasing complexity of tasks which require broad general knowledge and on the other hand a narrow specialization. Because of these conflicting principles modern education recognized the need for development of generic competences on the one hand, and information competences that match the modern information society on the other. In addition to education, which has recognized the need to develop generic and information competences, employers also pay great attention to these competences while hiring. In modern information society information competences become one of the fundamental basis for the development of other generic competences. Information and generic competences are directly linked because information is a fundamental element of learning which is based on the collection, organization, search and interpretation of acquired information. Development of modern information environment is characterized by growing complexity in quantitative and qualitative terms that require additional research of information competences required for the transition from the tertiary education sector to the labour market. This paper presents a survey of students' attitudes about the development of information competences during the study and their opinions about necessary information competences for their future professional careers.